Modeling adoption dynamics in social networks - LUU, Minh Duc (Institutional Knowledge at Singapore Management University, 2017)
This dissertation studies the modeling of user-item adoption dynamics where an item can be an innovation, a piece of contagious information or a product. By “adoption dynamics” we refer to the process of users making decision choices to adopt items based on a variety of user and item factors. In the context of social networks, “adoption dynamics” is closely related to “item diffusion”. When a user in a social network adopts an item, she may influence her network neighbors to adopt the item. Those neighbors of her who adopt the item then continue to trigger more adoptions. As this progress unfolds over time, the item is diffused through the social network. This connection motivates us to study also item diffusion modeling.